1990
DOI: 10.1111/j.0022-3646.1990.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

FUNGAL CONTROL OF POPULATION CHANGES OF THE PLANKTONIC DIATOM ASTERIONELLA FORMOSA IN A SHALLOW EUTROPHIC LAKE1

Abstract: Parasitic fungi infected an Asterionella formosa Hass. population for 10 months of the year, during which time the population density of the alga was over 100 cells‐L−1. High injection rates of more than 20% of the cells were observed between February and July except on a few occasions such as late April and late June. Mortality of infected diatom cells was temperature dependent in dialysis tube culture experiments; the loss rate of field populations due to fungal injection also was affected by temperature. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…These fluctuations have been partly explained by abiotic factors, such as temperature (Barr & Hickman, 1967a;Masters, 1971a;Blinn & Button, 1973;Van Donk & Ringelberg, 1983;Sen, 1987a;Kudoh & Takahashi, 1990), light (Barr & Hickman, 1967a;Blinn & Button, 1973;Abeliovich & Dikbuck, 1977;Kumar, 1978b;Canter & Jaworski, 1979Bruning, 1991b, d;Kagami & Urabe, 2002), nutrients (Bruning, 1991a), pH (Sen, 1987a), turbulence (Doggett & Porter, 1996;Kuhn & Hofmann, 1999), and biotic factors, such as Daphnia grazing on fungal zoospores . There are two contrasting statements concerning the necessary environmental conditions for the development of a fungal epidemic.…”
Section: Conditions For Fungal Epidemicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These fluctuations have been partly explained by abiotic factors, such as temperature (Barr & Hickman, 1967a;Masters, 1971a;Blinn & Button, 1973;Van Donk & Ringelberg, 1983;Sen, 1987a;Kudoh & Takahashi, 1990), light (Barr & Hickman, 1967a;Blinn & Button, 1973;Abeliovich & Dikbuck, 1977;Kumar, 1978b;Canter & Jaworski, 1979Bruning, 1991b, d;Kagami & Urabe, 2002), nutrients (Bruning, 1991a), pH (Sen, 1987a), turbulence (Doggett & Porter, 1996;Kuhn & Hofmann, 1999), and biotic factors, such as Daphnia grazing on fungal zoospores . There are two contrasting statements concerning the necessary environmental conditions for the development of a fungal epidemic.…”
Section: Conditions For Fungal Epidemicsmentioning
confidence: 99%
“…This may be explained by the fact that several environmental parameters commonly change simultaneously in aquatic systems. In addition, host density effects may override the effects of other factors (Kudoh & Takahashi, 1990). Besides, several factors affect host-parasite dynamics in complex ways (Sen, 1988a;Bruning, 1991b;Doggett & Porter, 1996).…”
Section: Conditions For Fungal Epidemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them have been misidentified as protistan bacterivorous nanoflagellates, e.g., flagellates in the group of Bicosoeca, which are attached to phytoplankton but do not harm the algae (31-33). A few studies have demonstrated epidemic outbreaks of chytrids on phytoplankton, but mainly with particular emphasis on host-parasite interactions and coevolution (21,30,48). Thus far, observations of parasitic fungi were obtained by using phase-contrast light microscopy with live or Lugol's iodine preserved samples (30,39,48).…”
mentioning
confidence: 99%
“…A few studies have demonstrated epidemic outbreaks of chytrids on phytoplankton, but mainly with particular emphasis on host-parasite interactions and coevolution (21,30,48). Thus far, observations of parasitic fungi were obtained by using phase-contrast light microscopy with live or Lugol's iodine preserved samples (30,39,48). Such conventional microscopy allows observation of fungal sporangia or similar forms (especially in laboratory cultures) but is a poor approach for characterizing chytrid parasites in natural samples, at the complex community level.…”
mentioning
confidence: 99%